2019
DOI: 10.3389/fimmu.2019.00428
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Genes HLA-DRB1, HLA-DPB1, and HLA-DQB1 Are Associated With the Antibody Response to Inactivated Japanese Encephalitis Vaccine

Abstract: Aim: The objective of this study was to evaluate the association of the human leukocyte antigen (HLA) class II genes HLA-DRB1, HLA-DPB1, and HLA-DQB1 with the humoral immune response elicited by inactivated Japanese encephalitis (JE) vaccine (IJEV).Methods: A total of 373 individuals aged 3–12 years in the Inner Mongolia Autonomous Region in China, who received two doses of IJEV at 0 and 7 days, were enrolled in the current study. Based on the individuals' specific JE virus (JEV)-neutralizing antibodies (NAbs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…In this way, we observed two particularly interesting immune genes (HLA-DPB1 and IL6) that contained multiple DMPs differing between high and low vaccine responders. Hypomethylation of HLA-DPB1 as found in high compared with low vaccine responders may indeed strengthen the overall immune response as previously demonstrated by the contribution of HLA to cellular host immunity in response to anthrax vaccine adsorbed [33]; rubella vaccine [34]; hepatitis B vaccine; and the inactivated Japanese encephalitis vaccine [35]. Additional evidence connecting HLA genotype and expression to vaccine immune responses was found in measles seropositive and seronegative individuals [36].…”
Section: Discussionsupporting
confidence: 60%
“…In this way, we observed two particularly interesting immune genes (HLA-DPB1 and IL6) that contained multiple DMPs differing between high and low vaccine responders. Hypomethylation of HLA-DPB1 as found in high compared with low vaccine responders may indeed strengthen the overall immune response as previously demonstrated by the contribution of HLA to cellular host immunity in response to anthrax vaccine adsorbed [33]; rubella vaccine [34]; hepatitis B vaccine; and the inactivated Japanese encephalitis vaccine [35]. Additional evidence connecting HLA genotype and expression to vaccine immune responses was found in measles seropositive and seronegative individuals [36].…”
Section: Discussionsupporting
confidence: 60%
“…As Japanese encephalitis vaccine be considered, our previous study investigated the association of HLA-DRB1, HLA-DPB1, and HLA-DQB1 with the humoral immune response elicited by the inactivated Japanese encephalitis vaccine (IJEV) and showed that HLA-DQB1 * 02:01 was significantly associated with JEV seropositivity (P < .05), while HLA-DQB1 * 02:02 was significantly associated with JEV seronegativity (P < .05). 14 In addition, we found that certain HLA-DRB1 and HLA-DPB1 alleles were associated with higher geometric mean titers (GMTs) than others. 14 The association study of cytokine gene variations with vaccine antibody response are particularly important in developing countries where JE is still a major health issue, because it may provide a clue for vaccine efficacy evaluation and new vaccine development.…”
Section: Introductionmentioning
confidence: 87%
“…14 In addition, we found that certain HLA-DRB1 and HLA-DPB1 alleles were associated with higher geometric mean titers (GMTs) than others. 14 The association study of cytokine gene variations with vaccine antibody response are particularly important in developing countries where JE is still a major health issue, because it may provide a clue for vaccine efficacy evaluation and new vaccine development.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Molecular genetic variations exert distinct influences on antigenspecific immune responses (29,32). The role of HLA genes as regulators of immune responses may also depend on the nature of the immune responses induced by different antigens (38,39). However, the identification of causal variants within the HLA region is intrinsically difficult due to the complex polymorphisms found in this region.…”
Section: The Role Of Hla Molecules As Immune Response Genes and The mentioning
confidence: 99%